Physical Characterisation of the Rainfed Aridisols of Punjab - Singh, C J; Singh, C B; Chaudhary, M R (Annals of Arid Zone, 2016)
Three profiles, representing two soil series of south west Punjab, were studied to identify physical constraints affecting crop production and to determine water storage. Soil texture ranged from loamy sand in Jassi Pauwali to sandy loam in Jodhpur Ramana I & II. None of these profiles showed physical constraints 10 root penetration. Final infiltration rale and field capacity of the profiles varied from 0.26 cm min-1 and 0.068 kg water per kg soil (0-180 cm depth) in Jassi Pauwali, and 0.5 cm min-1 and 0-180 kg water per kg soil (0-180 cm depth) in Jodhpur Ramana series.